THE EFFECT OF THE NUMBER OF MANPOWER AND GENERAL ALLOCATION FUNDS ON INEQUALITY IN ECONOMIC DEVELOPMENT OF WEST SULAWESI PROVINCE IN THE PERSPECTIVE OF ISLAMIC ECONOMICS IN 2016-2020 - Ummul Ummu Husnul; Junaiddin Zakaria; Dahlia Baharuddin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
How Islamic Economics View Inequality in Economic Development in West Sulawesi Province in 2016-2020. This study uses secondary data, which was obtained from the total number of regencies/cities in West Sulawesi Province from the 2016-2020 period. The results of this study indicate that: (1) the number of workers has a significant positive effect on inequality in economic development in Sulawesi province. West, (2) The Allocation of General Assistance Funds Has a Significant Positive Effect on Economic Development Inequality in West Sulawesi Province 2016.2020. The results of this study show that: the number of workers has an effect on the number of unemployed so that it has an impact on the growth rate of inequality in economic development in the province of West Sulawesi, then the amount of the allocation of general aid funds that are not evenly distributed causes development gaps in the regions, so this has an impact on the growth rate of inequality. Economic Development in West Sulawesi Province 2016-2020.